Primary headache types in adult epilepsy patients - Katharina Schiller; Markus Rauchenzauner; Tamir Avidgor; Sana Hannan; Carlo Lorenzen; Manuela Kaml; Gerald Walser; Iris Unterberger; Vera Filippi; Gregor Broessner; Gerhard Luef (European Journal of Medical Research, 2023)
Abstract Background Headache is among the most common comorbidities in epilepsy. This study examined the distribution of different primary headache disorders in a large cohort of patients with diagnosed epilepsy. Headache types were analysed with regard to gender, type of epilepsy and antiepileptic drugs (AEDs). Methods In this prospective single-centre study, 500 patients with epilepsy (250 female, mean age: 45.52 ± 17.26 years) were evaluated with regards to primary headache types using a validated German headache questionnaire categorizing for migraine (MIG), tension-type headache (TTH) or trigeminal autonomic cephalalgias (TAC), their combinations and unclassifiable headache. Data regarding type of epilepsy, seizure-associated headache, AED treatment and seizure freedom were collected. Results Of 500 patients with epilepsy, 163 (32.6%) patients (108 female and 55 male) reported suffering from headaches at least 1 day per month. MIG (without aura, with aura) and TTH were the most frequent headache type (MIG 33.1%, TTH 33.1%). Female epilepsy patients reported headaches significantly more often than male patients (x 2 = 8.20, p = 0.0042). In contrast, the type of epilepsy did not significantly affect headache distribution. Of 163 patients with headache, 66 (40.5%) patients reported seizure-associated headache and AEDs were used by 157 patients. Of importance, patients with AED monotherapy suffered from MIG less often when compared to patients on polytherapy (x 2 = 4.79, p = 0.028). Conclusion MIG and TTH are the most common headache types in epilepsy patients and headache is more frequent among female epilepsy patients. Monotherapy in AEDs might have a beneficial effect on the frequency of headache compared to polytherapy.